2014
DOI: 10.1180/minmag.2014.078.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Balićžunićite, Bi2O(SO4)2, a new fumarole mineral from La Fossa crater, Vulcano, Aeolian Islands, Italy

Abstract: Balićžunićite, ideally Bi 2 O(SO 4 ) 2 , is a new mineral found as a high-temperature fumarole sublimate (T = 600ºC) at La Fossa crater, Vulcano, Aeolian Islands, Italy. It occurs as aggregates of mm-sized prismatic and elongated crystals (~50 mm across and up to 200 mm long) associated with anglesite, leguernite, one other potentially new Bi-oxysulfate mineral, lillianite, galenobismutite, bismoclite, Cd-rich sphalerite, wurtzite, pyrite and pyrrhotite. Balićžunićite is colourless to white or pale brown, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Krivovichev et al (2013) reported that phases with structures containing oxo-centered tetrahedra also form in oxidation zones of mineral deposits, in which the formation of oxo and hydroxocentered Pb, Hg and Bi polynuclear clusters in aqueous solution determine the mobility of these metals. The formation of Bi-oxysulfates at Vulcano is not in contradiction with these results, as it is connected to local processes of oxidation due to atmospheric contamination of the volcanic gas phase (Garavelli et al, 2014;Pinto et al, 2014). In the fumarolic depositional environment of Vulcano, the general reducing conditions of the gaseous steam (Garavelli et al, 1997) at the time of sampling favored the transport of Bi from the magnetic chamber to the surface as Bi-Cl complexes rather than as OBi 4 complexes.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Krivovichev et al (2013) reported that phases with structures containing oxo-centered tetrahedra also form in oxidation zones of mineral deposits, in which the formation of oxo and hydroxocentered Pb, Hg and Bi polynuclear clusters in aqueous solution determine the mobility of these metals. The formation of Bi-oxysulfates at Vulcano is not in contradiction with these results, as it is connected to local processes of oxidation due to atmospheric contamination of the volcanic gas phase (Garavelli et al, 2014;Pinto et al, 2014). In the fumarolic depositional environment of Vulcano, the general reducing conditions of the gaseous steam (Garavelli et al, 1997) at the time of sampling favored the transport of Bi from the magnetic chamber to the surface as Bi-Cl complexes rather than as OBi 4 complexes.…”
Section: Resultsmentioning
confidence: 72%
“…During systematic investigations on high-temperature sublimates from the La Fossa crater at Vulcano (Aeolian Islands, Italy) collected in 1990 (T = 873 K), a very unique mineral assemblage consisting of some new anhydrous Bi sulfates was discovered. Two such phases have so far been described as new minerals: balićžunićite, Bi 2 O(SO 4 ) 2 (Pinto et al, 2014(Pinto et al, , 2015, and leguernite, Bi 12.67 O 14 (SO 4 ) 5 (Garavelli et al, 2014). During the examination of additional needle crystals from the same mineral assemblage from which leguernite was identified, two new Bi sulfates were discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The different sulfates can be distinguished by the number of bands and slightly different shifts of the characteristic SO 4 stretching (symmetric and antisymmetric) and bending modes in the 950-1200 and 400-700 cm -1 regions, respectively. That distinction is less palpable for the new phase I and cannonite, which, on the other hand, show very different Bi-O and lattice (Pinto et al 2013). Balićžunićite structural parameters and composition are diverse than those determined for the new phases found at Alfenza (see ahead).…”
Section: New Phase I (Hexagonal Platelets)mentioning
confidence: 91%
“…The north-western sector of the crater rim of La Fossa Crater is currently affected by intense fumarolic degassing, with outlet temperatures ranging from the boiling point of water up to 450 • C. The fumarolic fluids have a typical magmatic composition, with dry gas fraction dominated by CO 2 and with relevant concentrations of HCl, SO 2 , H 2 S, HF, and CO [32,33]. The mineralogy of the crater fumaroles is dominated by sulfides and sulfosalts, deposited due to a sublimate formation under high-temperature reducing conditions [34][35][36]. Notable quantities of ammonium minerals were also recognized [37].…”
Section: Sampling Areasmentioning
confidence: 99%